Pengaruh Orientasi Pelanggan dan Orientasi Teknologi terhadap Kinerja Bisnis pada Usaha Kecil dan Menengah (UKM) - Saputra, Suyono; Hendro (IPB University, 2024)
This study explores the influence of customer orientation and technology orientation on business performance in small and medium enterprises (SMEs) in Batam City. The purpose of this study is to analyze the role of customer orientation and technology orientation as the main factors influencing innovation capability and customer loyalty, which in turn impact SMEs' business performance. This study used purposive sampling method involving 302 respondents selected based on certain criteria. Data was collected through a questionnaire distributed online using Google Forms. The results showed that customer orientation has a significant influence on innovation capability and customer loyalty. Similarly, technology orientation contributes significantly to both variables. Innovation capability and customer loyalty proved to be important mediators in linking customer and technology orientation with business performance. With the integration of these two approaches, SMEs are able to improve operational efficiency, market competitiveness, and business sustainability. The results of this study provide theoretical contributions in expanding research related to SME business strategies and strategic recommendations for SME managers in Indonesia.